Analisis Hasil Investasi Dana Asuransi Jiwa Syariah di Indonesia Periode 2014-2021 - Warto Warto; Sabik Khumaini (Al Maal: Journal of Islamic Economics and Banking, 2022)
This paper aims to analysis the management of Islamic Life Insurance funds in Indonesia. From the OJK report, it was found that the investment returns of Sharia Life Insurance funds often experience losses, even though when viewed from the assets and investment value they have the highest interest compared to Sharia General Insurance and Sharia Reinsurance. The data in this study were obtained from OJK and the financial statements of Indonesian Sharia Insurance companies. This research uses quantitative method. The results of the study indicate that the main factor causing investment losses in Sharia Life Insurance funds is the placement of funds, which is dominated by the Capital Market sector, which accounts for 80% of the total investment. Total investment losses during the period 2014-2021 amounted to Rp.-42,713 billion. Total profit is Rp. 61,656 billion. So the total return on investment during this period is Rp. 18,943 billion of the total investment of Rp. 2.485 trillion or only 1%. The solution is that Sharia Life Insurance companies need to look for alternative financing sectors other than the Capital Market.